The effects of rubber nanoparticles with different polarities on thermal properties and foaming performance of polypropylene blends. Issue 52 (25th August 2020) - Tian, Bo; Li, Zhigang; Li, Jinfeng; Yao, Gang; Dong, Wei; Liu, Yuguang; Di, Mingwei
Abstract : Polypropylene blends with both polybutadiene rubber and polycarboxylbuturonile rubber and the required amount of acrylamide was prepared by blending with water, improve the foaming and thermal properties of polypropylene. Abstract : Polypropylene blends with both polybutadiene rubber (PB) and polycarboxylbuturonile rubber (xNBR) and the required amount of acrylamide (AM) was prepared by blending with water, and the crystallinity, rheological behaviour and thermal performance were analysed and compared. The results of DSC and XRD characterization showed an obvious enhancement in the crystallization of the PP matrix in PP/xNBR/AM blends compared to PP/PB/AM blends, due to the strong incompatibility between xNBR nanoparticles and the PP polymer matrix leading to the inhibition of segmental mobility and induced formation of heterogeneous nuclei. Rheological analysis showed that the dynamical mobility of polymer chains was retarded while the AM monomer was incorporated, due to strengthening interfacial interactions by grafts through hydrogen bonding. The foaming performance was clearly improved, as reflected in the uniform cell morphology and higher cell density, and the expansion ratio achieved was 13-fold. In addition, the decomposition temperature increased from 403 °C to 465 °C by nearly 62 °C as compared with neat PP, which is ascribed to the inhibition of segmental mobility due to the cyclization reaction of nitriles. The increase in the surface energy was about 2.2-fold, which resulted in a decrease of the water contact angle from 105.3° to 83.7°, attributed due to AM addition to the composition.